Porous hollow tubes processed by extrusion of ceramic emulsions - Vitorino, N
The processing of ceramic materials by extrusion is widely used to obtain products with constant cross section. Most of them are framed with applications as catalysis, filtration, building, fuel cells, isolators, etc., mainly if they are porous with special designed microstructural characteristics as pore size/distribution, liquid and gas permeability, mechanical properties, etc. Thus, in this work we combine a cellular ceramic preparation strategy based on a synergy of emulsification process and gel casting, with the extrusion process to obtain porous hollow tubes. Tree ceramic emulsions were extruded under different ram speeds and its effect was studied using Benbow Bridgwater model.